Penerapan Metode MOOSRA Dalam Penentuan Penerimaan Frontliner Menggunakan Pembobotan Metode ROC - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
In improving service efforts in an agency or service company, a responsible, dexterous, and well-informed frontliner is needed to communicate well with consumers so as to help the needs of these consumers. Not a few frontliners are unfriendly and also make consumers feel uncomfortable with the services provided by a frontliner so that it can have a bad impact on the company's agency. Therefore, this research was made to make it easier for company agencies to recruit frontliners who are friendly, polite, dexterous and responsible. To realize this, an effective and efficient system is needed in making a decision to recruit competent frontliners. The required system is called a decision support system. In the application of spk there are many methods that can be used, namely the WP, SAW, Electree, PSI, WASPAS, MOOSRA, TOPSIS, MOORA methods and there are also specific methods to find the value of the importance weight of each criterion such as ROC, AHP, Entrophy and others. a suitable method used in the problems in this study is the method used to recruit frontliners, namely the ROC and MOOSRA methods. The results after applying the ROC method are used to weight and find the importance value of each criterion and also use the MOOSRA method which is applied to find the ranking of each alternative that registers as a frontliner based on each criterion. After applying the two methods, namely the ROC and MOOSRA methods, it was produced that the best alternative was A8 with a preference value of 44.6195 and followed by alternative A1 with a preference value of 40.2737 and alternative A6 with a preference value of 39.8573. So, those who are eligible to graduate become frontliners on behalf of Ratih, Moci and Aldi